International adoption by individuals (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This contribution takes the form of a commentary on the judgment of the Const. Court, 21 March 2025, no. 33, by which the constitutional judges declared art. 29-bis, first paragraph, L. 4 May 1983, no. 184 (Right of the child to a family) to be constitutionally unlawful in the part in which, by referring to art. 6 adopt. law, it does not include single persons residing in Italy among those who may submit a declaration of willingness to adopt a foreign child residing abroad and ask the Juvenile Court of the district in which they reside to declare their suitability for adoption.
Keywords: International adoption; best interest; children rights; juvenile courts; right to have a family